2001
DOI: 10.1089/105072501750159651
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Prophylactic Treatment of Euthyroid Hashimoto's Thyroiditis Patients with Levothyroxine: Is There a Benefit?

Abstract: Studies in animal models of spontaneous Hashimoto's autoimmune thyroiditis (HT) show that prophylactic treatment with levothyroxine (LT4) can reduce incidence and degree of lymphocytic infiltration in HT. The aim of the present study was to clarify whether there is a benefit of prophylactic treatment with LT4 in patients with euthyroid HT with respect to the progression of the autoimmune process. Twenty-one patients with euthyroid HT were checked for thyroid function (thyrotropin [TSH], free triiodothyronine [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
14

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 29 publications
4
59
0
14
Order By: Relevance
“…Furthermore, elevated anti-TPO antibodies seemed to be more specific for thyroid disorder than elevated anti-TG, because they were associated with higher TSH levels. This confirms recent findings by Padberg et al (12). TSH elevations were also found in a group of patients without thyroid autoimmunity.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, elevated anti-TPO antibodies seemed to be more specific for thyroid disorder than elevated anti-TG, because they were associated with higher TSH levels. This confirms recent findings by Padberg et al (12). TSH elevations were also found in a group of patients without thyroid autoimmunity.…”
Section: Resultssupporting
confidence: 93%
“…The prophylactic usage of LT4 in euthyroid patients may suppress the serum concentrations of autoantibodies mildly because of a possible decline in antigenic stimulus (due to the rest) of the thyrocytes, not by direct suppression of antibodies (Padberg et al 2001). Neither corticosteroids nor nonsteroid anti-inflammatory drugs are indicated to inhibit chronic cellular destruction.…”
Section: Introductionmentioning
confidence: 99%
“…Padberg et al (2001) have reported reduction in anti-TPO antibodies and B lymphocyte counts in adults with eHT in response to levothyroxine prophylaxis.…”
Section: Discussionmentioning
confidence: 97%